Fluorine-containing fluorescent material, preparation method thereof and luminescent device

By coating the surface of fluoride phosphor with a hydrophobic layer and grafting basic groups, the problem of easy hydrolysis and corrosion of fluoride phosphor is solved, its resistance to hydrolysis and corrosion is improved, and the life of the light-emitting device is extended. service life.

CN119331605APending Publication Date: 2025-01-21JIANGSU BREE OPTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411373675.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing fluoride phosphors are prone to hydrolyzing and corroding components and components of light emitting devices in terminal applications, resulting in short service life.

Method used

A fluorine-containing fluorescent material is formed by coating the surface of fluoride phosphor with a hydrophobic layer and grafting a basic group on the surface of the hydrophobic layer. The pKa of the basic group is 7 to 12.

Benefits of technology

The hydrolysis resistance of the fluoride fluorescent material is improved, the corrosion to the light-emitting device is reduced, and the service life of the light-emitting device is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331605A_ABST
    Figure CN119331605A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a fluorine-containing fluorescent material, a preparation method thereof and a light-emitting device. The fluorine-containing fluorescent material comprises fluoride fluorescent powder, the molecular formula of the fluoride fluorescent powder is K2Si1-XMnxF6, x is smaller than 1, the surface of the fluoride fluorescent powder is coated with a hydrophobic layer, the surface of the hydrophobic layer is grafted with a basic group, and pKa of the basic group is 7-12. The fluorine-containing fluorescent material disclosed by the invention is high in hydrolysis resistance and is not easy to corrode a light-emitting device; the light-emitting device containing the fluorine-containing fluorescent material is long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of luminescent materials, and in particular, to a fluorine-containing fluorescent material and a preparation method thereof, and a light-emitting device. Background Art

[0002] In 1973, Paulusz of OSRAM in Germany first reported fluoride phosphor, which exhibits unique narrow-band emission near the wavelength of 630nm, so it has extremely high color purity and wide color gamut in backlight display; it has been widely used in backlight display packaging devices when combined with narrow-band green powder β-SiAlON.

[0003] However, the current fluoride phosphors still face many problems and challenges in the terminal application field. For example, fluoride phosphors are easily hydrolyzed, and fluoride phosphors are also easy to corrode the blue light chip, packaging glue and packaging bracket in the light-emitting device. Summary of the invention

[0004] The present application provides a fluorine-containing fluorescent material and a preparation method thereof, and a light-emitting device. The fluorine-containing fluorescent material in the present application has strong hydrolysis resistance and is not easy to corrode the light-emitting device; therefore, the light-emitting device containing the fluorine-containing fluorescent material in the present application has a long service life.

[0005] In a first aspect, the present application provides a fluorine-containing fluorescent material, which includes a fluoride fluorescent powder, wherein the molecular formula of the fluoride fluorescent powder is K 2 Si 1-X Mn x F 6 , x is less than 1, the surface of the fluoride phosphor is coated with a hydrophobic layer, the surface of the hydrophobic layer is grafted with basic groups, and the pKa of the basic groups is 7-12.

[0006] In the above technical solution, since the surface of the fluoride phosphor is coated with a hydrophobic layer, it is not easy for water to pass through the hydrophobic layer and contact the fluoride phosphor. The fluoride phosphor in the fluorine-containing fluorescent material is not easy to contact with water, and the fluoride phosphor is not easy to hydrolyze. In addition, the inventors also found that when the surface of the hydrophobic layer is grafted with basic groups, if part of the fluoride phosphor is hydrolyzed, a small amount of hydrogen fluoride produced by the hydrolysis (or hydrogen fluoride remaining when preparing the fluoride phosphor) will pass through the hydrophobic layer and react with the weakly basic groups on the surface of the hydrophobic layer to neutralize, so that the fluoride phosphor is not easy to corrode the components in the light-emitting device; and since the pKa of the basic group is 7 to 12, the weakly basic group can play a buffering role to protect the light-emitting device from being easily corroded by hydrogen fluoride, and at the same time, its weakly basic characteristics itself are not easy to corrode the light-emitting device.

[0007] In a possible implementation, based on the total mass of the fluorine-containing fluorescent material, the mass of the basic group accounts for 0.01% to 5% of the mass of the fluoride fluorescent powder.

[0008] In the above technical solution, the fluorine-containing fluorescent material that meets the above conditions is less corrosive to the light-emitting device.

[0009] In a possible implementation, the Mn content on the surface of the fluoride phosphor in contact with the hydrophobic layer is 0% to 1%.

[0010] In the above technical solution, the surface Mn content of the fluoride phosphor is low, which is beneficial to improving the anti-degradation performance of the fluorine-containing fluorescent material; especially when the Mn content is 0, the anti-degradation performance is the best.

[0011] In a possible implementation, the pKa of the basic group is 9-10.

[0012] In one possible implementation, the hydrophobic layer contains hydrophobic groups, and the hydrophobic groups include at least one of a polysiloxane group, a hydrocarbon group, an ester group, a polyoxypropylene group, and a perfluoroalkyl group having a carbon number greater than 12; optionally, the siloxane group is provided by at least one of a long-chain alkyl group such as hexadecyltrimethoxysilane and dodecyltrimethoxysilane.

[0013] In the above technical solution, polysiloxane, hydrocarbon, ester, polyoxypropylene, and perfluoroalkyl with carbon atoms greater than 12 have good hydrophobic properties, and the hydrophobic layer formed has excellent hydrophobic effect. In particular, the siloxane group, when combined with fluoride fluorescence, can make the effect of fluorine-containing fluorescent materials better.

[0014] In a possible implementation, the basic group includes at least one of nitrogen-containing bases such as amino, ethylenediamine, amide, fatty amine, and amidine.

[0015] In the above technical solution, the pKa of the above basic groups is in the range of 7 to 12, which is not easy to corrode the light-emitting device and can also protect the light-emitting device from being corroded by hydrogen fluoride.

[0016] In a possible implementation, the median particle size of the fluoride phosphor is 0.5 μm to 45 μm.

[0017] In the above technical solution, when the median particle size of the fluoride phosphor is 15 μm to 45 μm, it is more conducive to preparing a light-emitting device with high efficiency.

[0018] In a possible implementation, the hydrophobic layer has a thickness of 0.1 μm to 2 μm.

[0019] In the above technical solution, the thickness of the hydrophobic layer is within the above range, which is beneficial to ensure that the fluoride phosphor is not easy to absorb water and deliquesce, and at the same time will not affect the luminous intensity of the fluoride phosphor.

[0020] In a second aspect, the present application provides a method for preparing a fluorine-containing fluorescent material, which comprises the following steps: uniformly mixing a fluoride fluorescent powder, a hydrophobic agent and an organic solvent and drying the mixture to obtain a coating; then reacting the coating with a base to graft a basic group on the surface of the coating; wherein the molecular formula of the fluoride fluorescent powder is K 2 Si 1-X Mn x F 6 , x is less than 1, and the pKa of the grafted basic group is 7-12.

[0021] In the above technical solution, the prepared fluorine-containing fluorescent material has strong hydrolysis resistance and is not easy to corrode the light-emitting device.

[0022] In a third aspect, the present application provides a light-emitting device comprising the above-mentioned fluorine-containing fluorescent material.

[0023] In the above technical solution, the light-emitting device containing the above fluorine-containing fluorescent material has a long service life, high color purity and a wide color gamut. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 is a SEM image of the fluoride phosphor in Example 1 of the present application;

[0026] Figure 2 This is a SEM image of the fluorine-containing fluorescent material in Example 1 of the present application;

[0027] Figure 3 This is a comparison of the corrosion of LED chips before and after fluoride coating. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0029] In the prior art, although fluoride phosphors have unique narrow-band emission and can be used to prepare light-emitting devices with high color purity and color gamut, they are easily hydrolyzed and easily corrode components and parts in light-emitting devices, which brings challenges and risks to the popularization of fluoride phosphors.

[0030] In order to solve the problem that fluoride phosphors in the prior art are easy to hydrolyze and corrode light-emitting devices, the present application provides a fluorine-containing fluorescent material that is not easy to hydrolyze and not easy to corrode light-emitting devices. The light-emitting device containing the fluorine-containing fluorescent material of the present application not only has extremely high color purity and extremely wide color gamut, but also has a relatively long service life.

[0031] The fluorine-containing fluorescent material and the preparation method thereof according to the embodiments of the present application are described in detail below.

[0032] The fluorine-containing fluorescent material of the present application includes fluoride fluorescent powder, the molecular formula of which is K 2 Si 1- X Mn x F 6 , x is less than 1, the surface of the fluoride phosphor is coated with a hydrophobic layer, and the surface of the hydrophobic layer is grafted with basic groups, wherein the pKa of the basic groups is 7-12.

[0033] It should be noted that the fluoride phosphor K in this application 2 Si 1-X Mn x F 6 It means that potassium fluorosilicate is doped with manganese, which is reflected in the crystal structure as: a small amount of Mn 4+ Replace SiF 6 The octahedral center is formed by Si, so K 2 Si 1-X Mn x F 6 It is also commonly written as K 2 SiF 6 :Mn 4+ , which can also be referred to as KSF.

[0034] The inventors found that the following reactions occur when fluoride phosphor is hydrolyzed:

[0035]

[0036] [MnF 6 ] 2- (aq)+4H 2 O(l)→Mn(OH) 4 (s)+4H + (aq)+6F - (aq);

[0037] Mn(OH) 4 (s)→MnO 2 +2H 2 O(l).

[0038] During the hydrolysis process, H + It has strong corrosiveness and will corrode the packaged chip, metal electrode and silver-plated layer at the bottom of the package bracket in the light-emitting device, thereby reducing the service life of the light-emitting device. Since the surface of the fluoride phosphor in the present application is coated with a hydrophobic layer, it is not easy for moisture to pass through the hydrophobic layer and contact the fluoride phosphor, and the fluoride phosphor in the fluorine-containing fluorescent material is not easy to hydrolyze. In addition, the surface of the hydrophobic layer is grafted with a basic group with a pKa of 7 to 12. The alkalinity of this basic group is relatively weak and it is not easy to corrode the light-emitting device. It can also combine with HF to play a buffering role; therefore, even if the fluoride phosphor is hydrolyzed to produce HF or HF remains in itself, HF will pass through the hydrophobic layer and combine with the basic group, and it is not easy to corrode the light-emitting device. Specifically, the basic group includes at least one of the nitrogen-containing bases such as amino, ethylenediamine, amide, fatty amine, and amidine; preferably, the basic group has a pKa in the range of 9 to 10. Taking the amino group as an example, the nitrogen atom in the amino group has 8 electrons in the outer layer, which is very easy to react with the proton H + In this way, a buffer layer can be formed between the fluoride phosphor and the light-emitting device. In a high temperature and high humidity environment, even if the fluoride phosphor is hydrolyzed, the released HF can combine with the basic group amino group to protect the entire light-emitting device from being easily corroded.

[0039] In some embodiments of the present application, most of the manganese ions in the fluoride phosphor are distributed inside the fluoride phosphor, and there is no or almost no manganese ion distributed on the surface of the fluoride phosphor. Usually, the surface Mn content of the fluoride phosphor in contact with the hydrophobic layer is 0% to 1%, which is conducive to improving the anti-degradation performance of the fluorine-containing fluorescent material. In particular, when the surface Mn content is 0, the anti-degradation performance is the best. In addition, in some embodiments of the present application, the median particle size of the fluoride phosphor is 15μm to 45μm, which can be adapted to the application of LED light-emitting devices. In addition, in order to efficiently achieve no active corrosion to the device, the mass of the basic group in the fluoride fluorescent material accounts for 0.01 to 5% of the mass of the fluoride phosphor, which can be specifically regulated during the preparation process so that the mass content of the basic group and the fluoride phosphor satisfies the above relationship. It should be noted that in this application, the equivalent volume particle size is used to characterize the particle size of the particle, that is, the particle size of the particle to be measured is equal to the diameter of a spherical particle with the same volume as the measured particle.

[0040] In some embodiments of the present application, the hydrophobic layer contains hydrophobic groups, such as at least one of a siloxane group, a hydrocarbon group, an ester group, a polyoxypropylene group, and a long-chain perfluoroalkyl group (i.e., the number of carbon atoms is greater than 12). The siloxane group is generally derived from a silane coupling agent. Specifically, the silane coupling agent can be at least one of a long-chain alkyl group such as hexadecyltrimethoxysilane and dodecyltrimethoxysilane. Among them, the silane coupling agent has a better hydrophobic effect and also has a good synergistic effect with the amino group, which can better prevent moisture from entering the interior of the fluorine-containing fluorescent material. In addition, in some embodiments of the present application, the thickness of the hydrophobic layer is usually in the range of 0.1μm to 2μm, which is more conducive to blocking moisture, and does not affect the luminous intensity of the fluorine-containing fluorescent material.

[0041] The present application also provides a method for preparing a fluorine-containing fluorescent material, which comprises the following steps:

[0042] S100, mixing the fluoride phosphor, the hydrophobic agent and the organic solvent uniformly and drying them to obtain a coating body.

[0043] In this step, the hydrophobic agent is used to form the above-mentioned hydrophobic layer; the organic solvent plays the role of dissolving the hydrophobic agent, so that the hydrophobic agent can be more evenly coated on the surface of the fluoride phosphor in the subsequent process, thereby forming a hydrophobic layer with a relatively uniform thickness. The organic solvent can be at least one of acetone, dichloromethane, etc. The specific operation of this step is as follows:

[0044] Firstly, the hydrophobic agent is fully dissolved in the organic solvent, and then the fluoride phosphor is added and stirred to make it evenly mixed. After precipitation, the supernatant is poured out, and then an alcohol solvent is added for washing, and then the washing is dried to obtain the coating body.

[0045] In addition, in this step, the fluoride phosphor is self-made, and its preparation process is usually to mix different masses of K 2 Mn 6 Dissolve them in fluorosilicic acid solutions of the same mass and concentration to prepare BX solutions of different mass concentrations; then 2 Mn 6 In order from large to small mass concentration, BX solutions of different mass concentrations are injected into hydrogen fluoride solution, and the lower layer of liquid is collected after standing and stratification, and the lower layer of liquid is washed and dried to obtain fluoride phosphor. Specifically, taking the fluoride phosphor with a median particle size of 30 μm and a surface (i.e., the surface that contacts the hydrophobic layer later) with a Mn element content of 0 as an example, the preparation method is as follows:

[0046] S110, Preparation of BX n Solution: Weigh K 2 Mn 62.7g, 2.52g, 2.34g, 2.16g, 1.98g, 1.80g, 1.62g, 1.44g, 1.26g, 1.08g, 0.9g, 0.72g, 0.54g, 0.36g, 0.18g and 0g were respectively dissolved in 50g of 30% to 32% hydrofluorosilicic acid aqueous solution to obtain 16 groups of mixed solutions, which were numbered in sequence corresponding to BX 1 Solution~BX 16 , the larger the number, K 2 Mn 6 The less the content, the more BX 1 The solution contains 2.7 g K 2 Mn 6 , BX 16 Does not contain K 2 Mn 6 .

[0047] S120. Prepare solution A: weigh 21 g of potassium bifluoride and dissolve it in 250 ml of 40% hydrofluoric acid aqueous solution to obtain solution A.

[0048] S130, press the prepared BX solution into BX 1 Solution to BX 16 The solutions were injected into solution A at a rate of 10 mL / s, and different BX n The solution was injected at intervals of 6 minutes. The solution was stirred for 2 hours at 40°C and allowed to stand for stratification.

[0049] S140, post-treatment: pour out the supernatant, add 5% hydrofluoric acid aqueous solution, stir and wash twice, then wash twice with anhydrous ethanol, and dry under 60°C forced air drying conditions to obtain fluoride phosphor with a median particle size of 30 μm, and there is no Mn element on the surface of the fluoride phosphor.

[0050] If the size of the median particle size is to be changed, the concentration of potassium bifluoride solute in solution A needs to be adjusted. The higher the concentration, the smaller the particle size of the fluoride phosphor obtained. For example, adjusting 21g of potassium bifluoride to 31.5g will result in a fluoride phosphor with a median particle size of 15μm.

[0051] Of course, step S100 can also be performed by purchasing commercially available fluoride phosphors, but the surface of commercially available fluoride phosphors usually contains Mn elements, and their anti-degradation ability is relatively poor.

[0052] S200, mixing and reacting the coating body and the base to graft a basic group on the surface of the coating body, wherein the pKa of the grafted basic group is 7-12.

[0053] In some embodiments of the present application, when grafting the basic group in this step, the base used generally includes at least one of liquid ammonia, ethylenediamine, amidine, etc. As an example, taking liquid ammonia as an example, the operation process of this step is specifically as follows:

[0054] Under a helium pressure of 0.5 MPa to 2 MPa, the coating body and liquid ammonia are placed at 100° C. to 150° C. for reaction for 6 h to 24 h, and then dried.

[0055] When the fluorine-containing fluorescent material of the present application is used in a light-emitting device, the light-emitting device is not easily corroded and has a good service life.

[0056] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0057] Example 1

[0058] This embodiment provides a method for preparing a fluoride phosphor (i.e., a fluorine-containing fluorescent material) encapsulating a hydrophobic layer and a weak base group as follows:

[0059] (1) 2 g of hexadecyltrimethoxysilane was placed in 200 g of acetone solvent and stirred for 30 min to fully dissolve it. Then, 50 g of fluoride phosphor with a median particle size of 30 μm (the preparation method is described above in this article) was added to the acetone solvent and stirred for 2 h. After precipitation, the supernatant was poured out, and 200 g of ethanol was added for washing. After that, the coating was dried in a 60° C. forced air oven to obtain a coating. The hydrophobic layer of the coating was hexadecyltrimethoxysilane, and the thickness of the hydrophobic layer was 0.5 μm.

[0060] (2) Add the fluoride phosphor encapsulated with the hydrophobic layer (i.e., the coating) into a high-temperature and high-pressure reaction container with a Teflon coating, introduce helium protective gas into the container, then add 5 g of liquid ammonia, and react for 12 hours at 0.6 MPa and 100° C. After the reaction is completed, place it in a vacuum drying oven at -0.1 MPa and 60° C. for 6 hours to obtain the fluoride phosphor encapsulated with the hydrophobic layer and weak base groups.

[0061] Example 2

[0062] This embodiment provides a fluorine-containing fluorescent material, and the preparation method thereof is different from that of embodiment 1 in the following aspects:

[0063] (2) Add the fluoride phosphor encapsulated with the hydrophobic layer into a high-temperature and high-pressure reaction container with a Teflon coating, introduce nitrogen protective gas into the container, then add 2 g of ethylenediamine, and react for 12 hours at 0.6 MPa and 100° C. After the reaction is completed, place it in a vacuum drying oven at -0.1 MPa and 60° C. for 6 hours to obtain a fluoride phosphor encapsulated with a hydrophobic layer and weak base groups.

[0064] Example 3

[0065] This embodiment provides a fluorine-containing fluorescent material, and the preparation method thereof is different from that of embodiment 1 in the following aspects:

[0066] (1) 2 g of polyoxyethyl polyoxypropyl glyceryl ether was placed in 200 g of acetone solvent and stirred for 30 min to fully dissolve it. Then, 50 g of fluoride phosphor with a median particle size of 30 μm (the preparation method is described above in this article) was added to the acetone solvent and stirred for 2 h. After precipitation, the supernatant was discarded and 200 g of ethanol was added for washing. After that, the coating was dried in a 60° C. forced air oven to obtain a coating. The hydrophobic layer of the coating was polyoxyethyl polyoxypropyl glyceryl ether and the thickness of the hydrophobic layer was 0.5 μm.

[0067] Example 4

[0068] This embodiment provides a fluorine-containing fluorescent material, and the preparation method thereof is different from that of embodiment 1 in the following aspects:

[0069] In step (1), the same mass of dodecyltrimethoxysilane is used instead of hexadecyltrimethoxysilane.

[0070] Example 5

[0071] This embodiment provides a fluorine-containing fluorescent material. The preparation method thereof is different from that of embodiment 1. The main difference is that the fluoride fluorescent powder is different. The surface Mn content of the fluoride fluorescent powder in this embodiment is 0.05%. The specific preparation method of the fluoride fluorescent powder in this embodiment is as follows:

[0072] (1) Weigh 21 g of potassium bifluoride and dissolve it in 250 ml of a 40% hydrofluoric acid aqueous solution to obtain a solution A.

[0073] (2) Weigh K 2 Mn 6 20.5g was dissolved in 800g of 30% to 32% hydrofluorosilicic acid aqueous solution to obtain solution B.

[0074] (3) Inject the prepared solution B into solution A at an injection rate of 10 mL / s, stir for 2 h at 40 °C, and allow to stand to separate into layers.

[0075] (4) The supernatant was discarded, 5% hydrofluoric acid aqueous solution was added, stirred and washed twice, and then washed twice with anhydrous ethanol, and dried under a forced air drying condition of 60° C., thereby obtaining a fluoride phosphor with a median particle size of 30 μm and a surface Mn content of 0.05%.

[0076] Comparative Example 1

[0077] The fluoride phosphor in Example 1.

[0078] Comparative Example 2

[0079] The coating in Example 1.

[0080] Comparative Example 3

[0081] This comparative example provides a fluoride phosphor encapsulating a hydrophobic layer and a strong base group. The preparation method thereof is different from that of Example 1 in the following aspects:

[0082] The fluoride phosphor encapsulating the hydrophobic layer was added into a high-temperature and high-pressure reaction container with a Teflon coating, and the container was filled with helium protective gas, and then 2 g of guanidine (CH 5 N 3 ), reacted at 0.6Mpa and 100°C for 12 hours. After the reaction, it was placed in a vacuum drying oven at -0.1Mp and 60°C for 6 hours to obtain a fluoride phosphor containing a hydrophobic layer and a strong base group encapsulation.

[0083] Comparative Example 4

[0084] This comparative example provides a fluoride phosphor encapsulating a hydrophobic layer and a weak acid group. The preparation method thereof is different from that of Example 1 in the following aspects:

[0085] The fluoride phosphor encapsulated with a hydrophobic layer is added to a high-temperature and high-pressure reaction container with a Teflon coating, and the container is passed with helium protective gas, and then 2g of acetic acid is added, and the reaction is carried out for 12 hours under the conditions of 0.6Mpa and 100°C. After the reaction is completed, it is placed in a vacuum drying oven at -0.1Mp and 60°C for 6 hours to obtain a fluoride phosphor encapsulated with a hydrophobic layer and weak acid groups.

[0086] Comparative Example 5

[0087] The fluoride phosphor in Example 5.

[0088] Application Examples

[0089] Morphology test

[0090] The fluoride phosphor and the fluorine-containing fluorescent material in Example 1 were tested for their morphology using a SEM (Scanning Electron Microscope). The test results are shown in the figure. Figure 1 and Figure 2 shown.

[0091] As can be seen from the figure, the fluorine-containing fluorescent material ( Figure 2 ) compared to the unencapsulated fluoride phosphor ( Figure 1), the crystal particles after encapsulation have less obvious edges and corners, indicating that the encapsulation effect is better, and the phosphor particles are fuller and rounder, indicating that the encapsulation effect is more uniform.

[0092] Method for measuring thickness of hydrophobic layer in fluorine-containing fluorescent materials

[0093] The median particle size of the fluoride phosphor before and after coating was measured using a laser particle size analyzer, and the difference between the median particle size and the median particle size of the fluoride phosphor before and after coating can be regarded as the thickness of the coated hydrophobic layer.

[0094] Use performance testing

[0095] The fluorine-containing fluorescent materials of Examples 1 to 5 and the fluoride fluorescent powders, coatings and fluorine-containing fluorescent materials of Comparative Examples 1 to 5 were respectively packaged into lamp beads for double 85 reliability tests. The parameters during the tests are shown in Table 1, and the test results are shown in Table 2.

[0096] Table 1 Test parameters

[0097]

[0098] Table 2 Performance test results

[0099]

[0100]

[0101] It can be seen from the table that the degradation of the double 85 reliability test in the embodiments of the present application is not obvious, but the fluoride phosphors in Examples 1 and 5 without any encapsulation deteriorate more obviously, and the double 85 reliability of the surface without Mn is better than that of the surface with Mn. It can be seen from Example 1 and Comparative Example 2 that the double 85 performance of the fluorine-containing fluorescent material with surface encapsulated weak base groups is better than that of the hydrophobic coating only. In addition, it can be seen from Comparative Examples 3 and 4 that the double 85 reliability of strong base groups and weak acidic groups (PKa values ​​outside 7 to 12) is lower than the effect of encapsulation of weak base groups in the embodiments. It can be judged that the encapsulated fluoride phosphors in the embodiments of the present application have higher double 85 reliability and can provide better reliability for light-emitting devices.

[0102] Corrosion performance test:

[0103] 1 g of each of the fluoride phosphor, the fluoride phosphor with a hydrophobic layer, and the fluoride phosphor with a hydrophobic layer and a weak base group in Example 1 were dissolved in 15 ml of water, and then 5 LED blue light chips were added to each component and heated to 85° C. After 120 hours, the corrosion of the chips was observed. Figure 3 shown. Figure 3The top row shows the chip corrosion of the blank control group, the second row S1 shows the chip corrosion of a group of chips added with the fluoride phosphor in Comparative Example 1, the third row S2 shows the chip corrosion of a group of chips added with the coating in Comparative Example 2, and the fourth row S3 shows the chip corrosion of a group of chips added with the fluorine-containing phosphor material with encapsulated hydrophobic layer and weak base group in Example 1.

[0104] from Figure 3 It can be seen that the S2 fluoride phosphor and the S3 coating that only encapsulates the hydrophobic layer corrode the chip more seriously, and the electrode pins corrode and fall off after a long time, while the fluoride phosphor that encapsulates the hydrophobic layer and weak base groups has almost no corrosion to the chip. This shows that the fluorine-containing fluorescent material of the present application is not easy to corrode the chip even in a high temperature and high humidity environment.

[0105] The above are only embodiments of the present application and are not intended to limit the scope of protection of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of protection of the present application.

Claims

1. A fluorine-containing fluorescent material, characterized in that: It includes fluoride phosphor, the molecular formula of which is K2Si 1-X Mn x F6, x is less than 1, the surface of the fluoride phosphor is coated with a hydrophobic layer, the surface of the hydrophobic layer is grafted with a basic group, and the pKa of the basic group is 7-12.

2. The fluorine-containing fluorescent material according to claim 1, characterized in that: Based on the total mass of the fluorine-containing fluorescent material, the mass of the basic groups accounts for 0.01% to 5% of the mass of the fluoride fluorescent powder.

3. The fluorine-containing fluorescent material according to claim 1, characterized in that: The Mn content on the surface of the fluoride phosphor in contact with the hydrophobic layer is 0% to 1%.

4. The fluorine-containing fluorescent material according to claim 1, characterized in that: The pKa of the basic group is 9-10.

5. The fluorine-containing fluorescent material according to claim 1, characterized in that: The hydrophobic layer contains hydrophobic groups, which include at least one of a siloxane group, a hydrocarbon group, an ester group, a polyoxypropylene group, and a perfluoroalkyl group having a carbon number greater than 12; optionally, the siloxane group is provided by at least one of hexadecyltrimethoxysilane and dodecyltrimethoxysilane.

6. The fluorine-containing fluorescent material according to claim 1, characterized in that: The basic group includes at least one of an amino group, an ethylenediamine group, an amide group, a fatty amine group, and an amidine group.

7. The fluorine-containing fluorescent material according to claim 1, characterized in that: The median particle size of the fluoride phosphor is 0.5 μm to 45 μm.

8. The fluorine-containing fluorescent material according to claim 1, characterized in that: The thickness of the hydrophobic layer is 0.1 μm to 2 μm.

9. The method for preparing a fluorine-containing fluorescent material according to any one of claims 1 to 8, characterized in that: It includes the following steps: The fluoride phosphor, the hydrophobic agent and the organic solvent are mixed uniformly and dried to obtain a coating; the coating and the base are then mixed and reacted to graft basic groups on the surface of the coating; wherein the molecular formula of the fluoride phosphor is K2Si 1-X Mn x F6, x is less than 1, and the pKa of the grafted basic group is 7-12.

10. A light emitting device, characterized in that: It comprises the fluorine-containing fluorescent material according to any one of claims 1 to 8.